Factors associated with the level of prolactin in patients under remission from Alcohol Use Disorder: A gender perspective - Susmita Pandey; Ingeborg Bolstad; Lars Lien; Jørgen G. Bramness (Wiley, 2021)
Abstract Background Prolactin mirrors the dopaminergic activity in the brain which is key to understanding alcohol use disorders (AUD). Still, patients with AUD are a heterogenous group and there seem to be gender differences in the relationship between alcohol use and the level of prolactin. In this study, we examined gender‐wise relationship of alcohol use trait‐ and state‐related factors with the level of prolactin among AUD inpatients in remission. Methods This cross‐sectional study examined the level of prolactin along with general patient characteristics and alcohol use trait‐ and state‐related factors that could influence the level of prolactin in 112 AUD inpatients at three rehabilitation clinics in Norway. Logistic regression was performed to identify the gender‐specific predictors of level of prolactin. Results Male and female AUD patients had similar level of prolactin. Among females, younger age, early alcohol debut, and absence of parental drinking problem predicted higher level of prolactin. In males, presence of other substance dependence predicted a lower level of prolactin. Conclusions There were gender differences in the factors associated with the level of prolactin among the AUD patients. Especially in the female AUD patients under remission, alcohol use trait‐related factors were better predictors of the level of prolactin than the alcohol use state‐related factors, indicating that individuals might characteristically have varying degree of dopamine reactivity.